An investigation of strength degradation due to thickness plate reduction on Ferry Ro-Ro Ship's Hull. Issue 1 (November 2021) - Nugraha A, A M; Pawara, M U; Ardianti, A; Mahmuddin, F
Abstract: Old ships will experience a degradation of the structural strength after receiving repeated loads. Decreased strength performance is also caused by structure shape and structural dimensions changes. In steel ships, Dimensional changes will be discovered when the ship is docked, because the material undergo corrosion causing in thinning the shell plate. In this study, a thickness reduction of the shell plate has been simulated to determine the longitudinal response of the ship's structure. A Finite element analysis of ferry Ro-Ro ship's hull was carried out using ANSYS package program. The simulation was carried out to exceed the allowable limit for reducing the thickness plate by the Indonesian Classification Bureau (BKI), which is 20% of the initial plate thickness. Based on simulation result, it was found that an increase of stress at each variation of the reduction in hull plate thickness in hogging and sagging conditions.